Adjuvant chemotherapy for brain tumors delivered via a novel intra-cavity moldable polymer matrix - Rahman, Cheryl V.; Smith, Stuart J.; Morgan, Paul S.; Langmack, Keith A.; Clarke, Phil A.; Ritchie, Alison A.; Macarthur, Donald C.; Rose, Felicity R.A.J.; Shakesheff, Kevin M.; Grundy, Richard G.; Rahman, Ruman (Public Library of Science, 2013)
INTRODUCTION